L'évaluation comme objet de recherche dans les MOOC : prise en compte du contenu - Abdelkarim Zaid; Abdelghani Babori; Hicham Fassi-Fihri (Université de Provence, 2019)
This article presents a literature review of the assessment in research on MOOC by reviewing research articles published between January 2012 and January 2018. More specifically, it examines how previous researches address the question of assessment: is it mentioned or constituted a fully-fledged research object and if so how? The thematic analysis of 17 previous literature reviews and 76 empirical articles shows that assessment is little mentioned as a research object in its own right. Content was little considered as a research object in these articles.